2019
DOI: 10.1016/j.clinthera.2019.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study on the Association of Biomarkers With Real-world Outcomes of Omalizumab-treated Patients With Allergic Asthma

Abstract: Purpose: Biomarkers, including blood eosinophils (EoS) and fractional exhaled nitric oxide (FeNO), may affect omalizumab outcomes in allergic asthma, but evidence in the literature remains mixed. This study assessed omalizumab outcomes in real-world patients with allergic asthma stratified by pretreatment biomarker levels. Methods: Patients with allergic asthma aged 12 years initiated on omalizumab with 12 months of data after index were identified in the Allergy Partners electronic medical records (2007e2018)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
3
4
0
1
Order By: Relevance
“…We found that FeNO was not a useful biomarker to predict the effectiveness of omalizumab. Our results were similar to the results of a retrospective study 25 that enrolled 56 allergic asthma patients, and the results of the PROSPERO real-world study, 24 which was a prospective study that enrolled 806 patients with allergic asthma.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found that FeNO was not a useful biomarker to predict the effectiveness of omalizumab. Our results were similar to the results of a retrospective study 25 that enrolled 56 allergic asthma patients, and the results of the PROSPERO real-world study, 24 which was a prospective study that enrolled 806 patients with allergic asthma.…”
Section: Discussionsupporting
confidence: 86%
“…The PROSPERO study by Casale et al , 24 the retrospective study by Kavati et al , 25 and the STELLAIR study by Humbert et al 26 showed that peripheral blood eosinophils cannot be used as a biomarker for omalizumab responsiveness. However, in the EXTRA study, 23 the response to omalizumab therapy was better in the high peripheral blood eosinophil subgroup than in the low eosinophil subgroup, indicating that patients with a high eosinophil count may benefit from omalizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies which have not found an association between these biomarkers and the response to omalizumab [92,93,170]. However, the majority of the studies demonstrate such an association, with the high levels of blood eosinophils and FeNO and, to a lesser degree, of serum periostin to be associated with higher response rates to the treatment with omalizumab in terms of symptom and exacerbation control, OCS usage, hospital admissions and lung function [90,169,[171][172][173][174][175]. Moreover, histological and immunological studies of the airways have shown that omalizumab reduces the mucosal concentration of IgE and the tissue eosinophil cell density [176].…”
Section: Association Of Biomarkers With Outcomes Of Omalizumab-treate...mentioning
confidence: 99%
“…Patients with severe allergic asthma often experience a significant decline in lung function. Despite the fact that some studies have not found a significant improvement in forced expiratory volume in 1 s (FEV1) after the initiation of omalizumab [118,166,[183][184][185][186][187][188][189], the majority of the studies have exhibited a significant improvement in FEV1 after the initiation of omalizumab in asthmatic patients both as a whole [17,29,32,33,59,60,67,73,81,86,119,152,153,158,162,173,[190][191][192][193][194][195][196][197][198], and in specific groups such as children [199], obese patients [200], patients with fixed airway obstruction [201], patients with various co-morbidities [202], and even non-atopic patients with asthma [87]. Similar improvements after the initiation of omalizumab have also been observed in forced vital capacity (FVC) [33,203], FEV1/FVC ratio [59,73], peak expiratory flow (PEF) [19,86,…”
Section: Omalizumab and Lung Functionmentioning
confidence: 99%